Wybrane zagadnienia rytmiczne w edukacji jazzowej = Selected rhythmic issues in jazz education in the context of performative and interpretative problems - Pernal, Bartosz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is dedicated to selected rhythmic issues in jazz improvisation in the context of music education. The author explains important terms, the proper definition which allows to better understand the language of jazz in the area of rhythm and shape the individual language of musical expression. Main issues discussed are timing and polymetry.
Keywords: jazz; rhythms; timing; swing; meter; improvisations; polymetry